Sources of Han décor : foreign influence on the Han dynasty Chinese iconography of paradise (206 BC - AD 220) /: foreign influence on the Han dynasty Chinese iconography of paradise (206 BC - AD 220). (2019) - Psarras, Sophia-Karin
No abstract available